Effects of functional resistance training on muscle strength and musculoskeletal discomfort - Cassemiro, Bruna Montechieze; Lemes, Ítalo Ribeiro; Figueiredo, Maria Paula Ferreira De; Vanderlei, Franciele Marques; Pastre, Carlos Marcelo; Netto Júnior, Jayme (Pontifícia Universidade Católica do Paraná, 2017)
AbstractIntroduction: Functional resistance training (FRT) is becoming increasingly popular to improve physical fitness of practitioners, however, yet there are gaps in knowledge about effectiveness of FRT in relation conventional resistance training (CRT) in several ambits, as musculoskeletal complaints.Objective: Compare the effect of FRT and CRT in the musculoskeletal discomfort and magnitude of gain in muscle strength in healthy women.Methods: 52 women was divided into three groups, FRT (n = 15; 22 ± 2.35 years): functional resistance training; CRT (n = 14; 22.5 ± 1.78 years): conventional resistance training and CG (n = 13; 20.6 ± 1.10 years): no type of intervention. The training was periodized in 30 sessions over 12 weeks with 3 sessions per week. For the muscle strength variable used the 1RM test and for the musculoskeletal discomfort variable, the Nordic Musculoskeletal Questionnaire (NMQ). Regarding the statistical analysis, all results took into consideration a 5% level of significance.Results: Considerable gain in muscle strength was observed for all exercises in both training groups. In addition, there was a tendency in CRT to relate a more musculoskeletal discomfort; presented 27.3% more complaints compared FRT in the MNQ.Conclusion: The FRT was as effective as the CRT for improving muscle strength, furthermore, there was a tendency for FRT to cause less musculoskeletal discomfort.

ResumoIntrodução: O treinamento resistido funcional (TRF) está se tornando cada vez mais popular para melhorar a aptidão física dos praticantes, entretanto, ainda não está totalmente esclarecido sobre a eficácia do TRF em relação ao treinamento resistido convencional (TRC) em diversos âmbitos, como queixas de desconforto osteomuscular.Objetivo: Comparar o TRF e TRC nas queixas de desconforto osteomuscular e na magnitude de ganho de força muscular em mulheres saudáveis.Métodos: O estudo foi composto por 52 mulheres divididas em três grupos: TRF (n = 15; 22 ± 2.35 anos): treinamento resistido funcional, TRC (n = 14; 22.5 ± 1.78 anos): treinamento resistido convencional e GC (n = 13; 20.6 ± 1.10 anos): nenhum tipo de intervenção. O treinamento foi periodizado em 30 sessões durante 12 semanas com três sessões semanais. Para a variável força muscular utilizou-se o teste de 1RM e para as queixas osteomusculares, o Questionário Nórdico de Sintomas Osteomusculares (QNSO). Em relação a análise estatística, todos os resultados levaram em consideração o nível de 5% de significância.Resultados: Notou-se ganho considerável de força muscular para todos os exercícios em ambos os grupos de treinamento. Além disso, observou-se uma tendência no TRC a relatar um maior número de queixas osteomusculares, apresentando 27,3% mais queixas comparadas ao TRF no QNSO.Conclusão: O TRF foi tão eficaz quanto o TRC para melhorar a força muscular, e, ainda, houve uma tendência de que o TRF provoque menores quantidades de desconfortos osteomusculares.
Efeitos do treinamento resistido funcional na força muscular e desconforto musculoesquelético
Keywords: Strength Training; Exercise Movement Techniques; Musculoskeletal Pain; Muscle Strength; Treinamento de Resistência; Técnicas de Exercício e de Movimento; Dor Musculoesquelética; Força Muscular